Reforma tributária e federalismo fiscal: Uma análise das propostas de criaç\~ao de um novo imposto sobre o valor adicionado para o Brasil - Rodrigo Octávio Orair; Sérgio Wulff Gobetti (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This paper analyses two tax reform bills that are being discussed at the Brazilian National Congress, by comparing them and pointing their advantages and drawbacks. Moreover, the paper provides four empirical contributions to the debate: i) neutral rate estimates for the new Goods and Services Tax (GST) and its shares between federal entities and budget earmarks; ii) simulation of the new tax model transition rules; iii) regressivity measures of the single rate GST compared to the current model with differentiated rates, as well as cost estimates for implementing a mechanism to reimburse the tax paid by low income households; and iv) assessment of the potential impact on the revenue sharing between state and local governments.
Keywords: H25; H71; 330; educational service valuation; inequality; education; welfare; returns to education; hedonic pricing